Past, present and future of epilepsy - Funchal, Cláudia (2007)
Epilepsy is a complex brain disorder with diverse clinical features. Moreover, epilepsy is one of the most common serious neurological disorders worldwide with no age, racial, social class, national or geographic boundaries. This disease causes recurring seizures that happen when clusters of neurons in the brain send out wrong signals. A common way to explain seizures is that a disruption has ocurred in the normal balan- ce of excitation and inhibition. Using different experimental models, it is clear that genes, developmental mechanisms, and neural plasticity play major roles in creating a state of underlying hyperexitability. Epilep- sy patients may have strange sensations and emotions or behave strangely before a seizure occurs. Diffe- rent features of epileptic seizures have been reported, where the patients may have violent muscle spasms or lose consciousness. This is a disorder with many possible causes, making mechanistic predictions a challenge. Anything that disturbs the normal pattern of neuron activity - from illness to brain damage to abnormal brain development - can lead to epilepsy. Several experimental models have been developed wi- th the objective to gain insight into the mechanisms of disruption involved in epilepsy. Nonetheless, the target and/or mechanism of action of many of drugs used to control epilepsy remains unclear. Their eluci- dation should improve diagnosis and may provide new targets for the development of specifi c prophylactic therapies for epilepsy